Planning and controlling raw materials using the material requirements planning method - Ira Silfiani; Deasy Kartika Rahayu Kuncoro; Farida Djumiati Sitania (Jurnal Teknika, 2021)
The water treatment plant (IPAM) in Kampung Damai is one of nine water treatment plants owned by PDAM Tirta Manggar, Balikpapan City. In carrying out clean water treatment, IPAM Kp Damai requires water purification raw materials in alum, lime, and chlorine. Companies often experience shortages or accumulation of raw materials from the rest of the previous production, so that it has an impact on inventory and storage costs. Therefore, we need planning and control of raw materials to optimize the total cost of inventory. The method used in this study is the lot technique in material requirements planning, namely lot for lot and periodic order quantity. The type of data used is primary data and secondary data where the research was conducted. The data collection technique used is secondary data (historical data). The analysis technique used is plotting past demand data, forecasting, and material requirements planning. From the results of the study, it can be concluded that the application of the lot for lot method for each raw material for water purification at IPAM Kp. Damai PDAM Kota Balikpapan can minimize the total cost of inventory compared to the periodic order quantity method. Instalasi pengolahan air minum (IPAM) Kampung Damai merupakan salah satu dari sembilan instalasi pengolahan air minum yang dimiliki oleh PDAM Tirta Manggar Kota Balikpapan. Dalam melakukan pengolahan air bersih, IPAM Kp Damai membutuhkan bahan baku penjernih air berupa alum, kapur, dan kaporit. Perusahaan kerap mengalami kekurangan maupun penumpukan bahan baku dari sisa produksi sebelumnya, hal ini berdampak terhadap biaya persediaan dan penyimpanan. Oleh karena itu, dibutuhkan suatu perencanaan dan pengendalian bahan baku agar total biaya persediaan dapat dioptimalkan. Metode yang digunakan dalam penelitian ini adalah teknik lot dalam material requirement planning yaitu lot for lot dan periodic order quantity. Jenis data  yang digunakan adalah data primer dan data sekunder tempat penelitian dilakukan. Teknik pengumpulan data yang dilakukan adalah data sekunder (data historis). Teknik analisis yang dilakukan adalah memplot data permintaan di masa lalu, peramalan, dan material requirement planning. Dari hasil penelitian dapat diambil kesimpulan bahwa penerapan metode lot for lot untuk setiap bahan baku penjernih air pada IPAM Kp. Damai PDAM Kota Balikpapan dapat meminimumkan biaya total persediaan dibandingkan dengan metode periodic order quantity.